Spatialisation of non-linear narratives through intertextual reading - Ferry Gunawan (ARSNET, 2023)
This paper explores spatial strategies created through a non-linear continuity of narratives, instead of chronological ones. It employs the creation of multiple narrative possibilities by spatialisation mechanism as a new way of reading an intertextual narrative. This research explores different themes of spatial narratives based on the book Penguin Hate Stuff by Greg Stones. The study utilises the mechanism of spatial manipulation using horizontal and vertical axis towards the episodic events portrayed in the book, questioning the original intertextuality of the book's text, and opening up multiple re-interpretations. The explorations of non-linear narratives demonstrate strategies of spatialisation based on the stitched landscape, the opposition of roles, and collective multiverse possibilities. This study expands the current practice of narratives and architecture by re-reading narrative episodic events in a non-linear way, creating open-ended possibilities.